Relationship of Self-Efficacy with Therapeutic Regimen and Clinical/Laboratory Outcomes in Hemodialysis Patient - Rambod; Peyrovi; Sareban; F Rafii (Iran University of Medical Sciences, 2010)
Background and Aim : Self-efficacy in hemodialysis patients has been found to be associated with increased adherence to treatment and decreased physical, psychological and social problems. The aimof this study was to determine the relationship between therapeutic regimen self-efficacyand clinical/ laboratory outcomes as adherence in hemodialysis patients.   Material and Method: In this cross-sectional study, 200 hemodialysis patients were selected by convenience sampling method. The questionnaire, "Strategies used by people to promote health", assessed self-efficacy with therapeutic regimen.Clinical/Laboratory outcomes such as phosphate, nitrogen urea, potassium, calcium and weight gain between dialysis sessions were obtained from patients'medical records. Data were collected from hemodialysis patients in a teaching hospital affiliated to Iran University of Medical Sciences and Health Services. Data were analyzed by SPSS-14.   Results: self-efficacy with therapeutic regimen was positively related to laboratory outcomes such as phosphate, nitrogen urea, and potassium (P0.05). Also, weight gain between dialysis sessions was significantly correlated with self-efficacy (P<0.05).  Conclusion: The findings indicated that patients with greaterself-efficacy with therapeutic regimen had lower levels of serum potassium, phosphate, nitrogen urea and weight gain between two session of dialysis. Based on these findings, it was suggested to nurses for planning educational programs to increase self efficacy in patient with renal failure, therby, helping the patients to enhance self care and compliance with therapeutics regimen.